Changes of phenolic content in rapeseed during preliminary drying - Nogala Kalucka Malgorzata,; Siger Aleksander, (Journal of Oilseed Brassica, 2026)
Drying of rapeseed represents one of the most important elements in the complexity of actions defined asthe “post-cropping” process. This work investigates how drying of the rapeseed at low and high temperatureinfluences the bioactive compounds (phenolic acids). Samples of rapeseed (Kronos and Lisek variety) weredried at 60, 80, 100, and 120C and low temperature (layer 2 and 12). In methanolic extracts total phenoliccontent was determined using Folin-Ciocalteu reagent and composition of free phenolic acids was determinedby HPLC. Obtained results showed that the most unfavourable influence on the native hydrophilic antioxidantcontent was observed after drying at 60 and 80oC. Seed dried at these temperatures are characterized byhighest decrease of total phenolic compounds and free phenolic acid content. Probably it is caused by theactivity of enzymes (phenoloxidaze) that display optimal functional activity at this temperature